Chicken cGAS Senses Fowlpox Virus Infection and Regulates Macrophage Effector Functions - Oliveira, Marisa; Rodrigues, Damaris Ribeiro; Guillory, Vanaique; Kut, Emmanuel; Giotis, Efstathios S.; Skinner, Michael A.; Guabiraba, Rodrigo; Bryant, Clare E.; Ferguson, Brian J. (Frontiers in Immunology, 2021)
The anti-viral immune response is dependent on the ability of infected cells to sense foreign nucleic acids. In multiple species, the pattern recognition receptor (PRR) cyclic GMP-AMP synthase (cGAS) senses viral DNA as an essential component of the innate response. cGAS initiates a range of signalling outputs that are dependent on generation of the second messenger cGAMP that binds to the adaptor protein stimulator of interferon genes (STING). Here we show that in chicken macrophages, the cGAS/STING pathway is essential not only for the production of type-I interferons in response to intracellular DNA stimulation, but also for regulation of macrophage effector functions including the expression of MHC-II and co-stimulatory molecules. In the context of fowlpox, an avian DNA virus infection, the cGAS/STING pathway was found to be responsible for type-I interferon production and MHC-II transcription. The sensing of fowlpox virus DNA is therefore essential for mounting an anti-viral response in chicken cells and for regulation of a specific set of macrophage effector functions.